On migrants with migrants - Kurnik, Andrej (Teorija in praksa, 2021)
In which ways can we theorise the recent illegalised migrations in Europe? This article considers theoretical novelties in the field of migration studies that have emerged since the mass migration into the European Union seen in 2015. Methodologically, the authors combine critical (discursive) analysis with the testing of certain still relevant theoretical concepts that have yet to be applied in migration studies, based on fieldwork along the Balkan Route over the last 5 years. The analysis has shown that the defining and decisive feature of the recent illegalised migrations, insufficiently considered by migrations scholarship, is the political subjectivity and agency of the migrants. Recognition of such agency makes migration the site of the critique of global inequalities and the site of inclusive social transformation
Keywords: Balkan migrant route; Balkanska migracijska pot; država; Emigration and immigration; Izseljevanje in priseljevanje; migracije; migrations; political theory; politična teorija; state